2000
DOI: 10.1016/s0925-4773(00)00416-0
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the epithelial apical junctional complex during mouse preimplantation development: a role for rab13 in the early maturation of the tight junction

Abstract: We have investigated the mechanisms by which the epithelial apicolateral junctional complex (AJC) is generated during trophectoderm differentiation in the mouse blastocyst using molecular, structural and functional analyses. The mature AJC comprises an apical tight junction (TJ), responsible for intercellular sealing and blastocoel formation, and subjacent zonula adherens E-cadherin/catenin adhesion complex which also extends along lateral membrane contact sites. Dual labelling confocal microscopy revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…Internal punctate localization of ZO-1 was observed in one cell. Such ZO-1 localization has been observed during the development of the tight junction both in cell culture as well as in vivo (29,30).…”
Section: Ankyrin-g Polypeptides Are Associated With the Lateralmentioning
confidence: 75%
“…Internal punctate localization of ZO-1 was observed in one cell. Such ZO-1 localization has been observed during the development of the tight junction both in cell culture as well as in vivo (29,30).…”
Section: Ankyrin-g Polypeptides Are Associated With the Lateralmentioning
confidence: 75%
“…A model proposed by Barwe et al (29) suggests that the Na/K-ATPase ␣ subunit is able to phosphorylate p85, which recruits this subunit to the plasma membrane and results in activation of phosphatidylinositol 3-kinase and the generation of inositol 1,4,5-trisphosphate, which induces the binding of annexin II to the Na/K-ATPase ␤ subunit cytoplasmic tail, activation of the Rac1 RhoGTPase, and modifications to the actin cytoskeleton. Studies have shown that loss of tight junction structure and increased paracellular permeability is often linked to the disruption of the circumferential actin ring that is localized at the apical pole of polarized epithelial cells (42)(43)(44). In MDCK cells, loss of tight junction permeability upon Na ϩ /K ϩ -ATPase inhibition also is associated with reduced stress fiber content and reduced RhoA activity (34).…”
Section: Discussionmentioning
confidence: 99%
“…The transepithelial electrical resistance (TER) can be used to monitor the tightness of the seal between neighboring cells. Because the recruitment of Rab13 to the apicolateral junctional complex occurred at an early stage in the assembly of TJ (Zahraoui et al, 1994;Sheth et al, 2000), we postulated that it might be involved in TJ sealing. Therefore, we measured TER over a 120-h time period of parental MDCK, GFP, GFP-Rab13WT, GFP-Rab13T22N, and GFP-Rab13Q67L cells grown on filters (Figure 2).…”
Section: Expression Of Gfp-rab13q67l Delays the Formation Of Electricmentioning
confidence: 99%
“…Although the exact role of Rab proteins is still unclear, they may control the assembly of protein complexes involved in various cellular processes including vesicle movement and fusion or actin organization (Stenmark et al, 1995;Kato et al, 1996;Peränen et al, 1996;Ren et al, 1996;Echard et al, 1998;Nielsen et al, 1999;White et al, 1999). Recently, we have found that Rab13 is recruited to cell-cell contacts at an early stage of assembly of junctional complexes (Sheth et al, 2000), suggesting that Rab13 may be a good candidate for regulating the assembly cell-cell junctions. In this study, we investigate the role of Rab13 in TJ functions.…”
Section: Introductionmentioning
confidence: 99%